STROBE-metagenomics: a STROBE extension statement to guide the reporting of metagenomics studies. Issue 10 (October 2020) - Bharucha, Tehmina; Oeser, Clarissa; Balloux, Francois; Brown, Julianne R; Carbo, Ellen C; Charlett, Andre; Chiu, Charles Y; Claas, Eric C J; de Goffau, Marcus C; de Vries, Jutte J C; Eloit, Marc; Hopkins, Susan; et al.
Summary: The term metagenomics refers to the use of sequencing methods to simultaneously identify genomic material from all organisms present in a sample, with the advantage of greater taxonomic resolution than culture or other methods. Applications include pathogen detection and discovery, species characterisation, antimicrobial resistance detection, virulence profiling, and study of the microbiome and microecological factors affecting health. However, metagenomics involves complex and multistep processes and there are important technical and methodological challenges that require careful consideration to support valid inference. We co-ordinated a multidisciplinary, international expert group to establish reporting guidelines that address specimen processing, nucleic acid extraction, sequencing platforms, bioinformatics considerations, quality assurance, limits of detection, power and sample size, confirmatory testing, causality criteria, cost, and ethical issues. The guidance recognises that metagenomics research requires pragmatism and caution in interpretation, and that this field is rapidly evolving.